2017
DOI: 10.1596/1813-9450-7996
|View full text |Cite
|
Sign up to set email alerts
|

Who Should Be at the Top of Bottom-Up Development? A Case Study of the National Rural Livelihoods Mission in Rajasthan, India

Abstract: Vijayendra Rao (World Bank) March 2017 It is widely acknowledged that top-down support is essential for bottom-up participatory projects to be effectively implemented at scale. However, which level of government, national or sub-national, should be given the responsibility to implement such projects is an open question, with wide variations in practice. This paper analyzes qualitative and quantitative data from a natural experiment of a large participatory project in the state of Rajasthan in India comparing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The findings point towards the significant role of contextual intricacies in determining the impact of interventions on sustainable livelihoods (Ert€ or-Akyazi, 2019;Joshi and Rao, 2017). These contextual factors are interactive in nature (Ozturk, 2017;Devereux, 2016;Islam and Sato, 2012).…”
Section: Research Avenue 1 Studying the Context Of Livelihood Interve...mentioning
confidence: 89%
See 2 more Smart Citations
“…The findings point towards the significant role of contextual intricacies in determining the impact of interventions on sustainable livelihoods (Ert€ or-Akyazi, 2019;Joshi and Rao, 2017). These contextual factors are interactive in nature (Ozturk, 2017;Devereux, 2016;Islam and Sato, 2012).…”
Section: Research Avenue 1 Studying the Context Of Livelihood Interve...mentioning
confidence: 89%
“…The review suggests that there is a significant role of trade and market policies and importance of local institutions and practices in shaping rural and community livelihoods (Joshi and Rao, 2017;Wang et al, 2017;Tezzo et al, 2018;Allison and Horemans, 2006). One of the key syntheses of this review point towards the ongoing debates between formal and informal institutions (Ert€ or-Akyazi, 2019; Frey et al, 2019;Babulo et al, 2009).…”
Section: Institutional Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, what is considered "North" India also has five times as many people as the South and is extraordinarily diverse. For instance, the state of Rajasthan has a long history of civic movements (Joshi and Rao 2017) and village councils that have been active for a long time (Krishna 2002). Rural citizens in Rajasthan make claims on the state in much the same way as rural citizens in the South by expanding their repertories of action that work across traditional networks (Krishna 2002;Krusk-Wisner 2018).…”
Section: South India Vs North Indiamentioning
confidence: 99%
“…This study contributes to the literature on development policy discourse as well as quantitative assessments of SEWB. One stream of literature focuses on perceived utility and explains the role of relative incomes and inequalities (Asri, 2019;Das, 2016;Joshi & Rao, 2017;Piketty, 2014), while another stream of literature underscores ambiguous association between economic development and perceived economic wellbeing (e.g., Easterlin, 1974;Rajan, 2019;Stevenson & Wolfers, 2013). The insights are combined and then concluded that while development policy does matter in driving SEWB, integrated policy design could perhaps more likely to enhance the sense of SEWB.…”
Section: Introductionmentioning
confidence: 99%